Specific Parameters of Toxic Reactions in Rats to the Combination of Delamanid and Drugs for Treatment of Drug Resistant Tuberculosis (A Pilot Study) - G. N. Mozhokina; L. Yu. Petrova; A. G. Samoylova; A. V. Abramchenko (Туберкулез и болезни лёгких)
The objective: to evaluate the toxicity of combinations of delamanid and drugs for treatment of drug resistant tuberculosis with different safety profiles in an experiment.Results. During 14 days of the study, the animals of both experimental groups satisfactorily tolerated the administration of drug combinations, no animals died, and no negative impact on body weight changes was observed (physiological weight gain). In rats from Group OG-1, the change in the skin color (orange tint) was noted.This change in the tissue color is an adverse reaction, but according to the literature [4], it is reversible. The prolongation of QT interval on ECG in rats treated with the combination of drugs with cardiotoxic potential (Dlm, Bdq, Cfz, Pto) was insignificant, and with the combination of Dlm, Lzd, Cs, Pto did not differ from the baseline level. The neurotoxicity of the combination of Dlm, Lzd, Cs, Pto combination manifested through a decrease in motor and exploratory activity. A decrease in exploratory activity in rats treated with Dlm, Bdq, Cfz, Pto was observed against the background of the preservation of their motor activity. There were no significant changes in laboratory and morphometric parameters in both experimental groups compared to the control group.